Acupoint massage on meridians in the treatment of insomnia of heart and spleen deficiency type after stroke (经穴推拿技术治疗中风后心脾两虚型失眠1例的护理体会) - YANG Yu (杨宇); HU Shirong (胡世荣); WANG Haibo (王海波); WANG Xuesong (王雪送); FAN Yan (范艳); XU Jingjin (徐京巾); TANG Ling (唐玲) (中西医结合护理)
This paper summarized the effect observation of acupoint massage on meridians and related nursing measures for a patient with insomnia of heart and spleen deficiency type after stroke. The basic nursing and psychological care were carried out to ensure the patient safety and improve the quality of life during the treatment. Based on the Traditional Chinese Medicine syndrome differentiation, the acupoint massage therapy is considered as an safe and effective intervention in relief of insomnia of heart and spleen deficiency type after stroke. (本文总结采用经穴推拿技术改善中风后心脾两虚型失眠的护理经验, 包括推拿的操作方法、心理护理以及常规基础护理等。推拿治疗具有绿色、安全、患者易于接受的特点, 患者依从性高, 基于中医辨证施护, 能有效改善中风后心脾两虚型失眠症状, 提高患者生活质量。)